Evaluation of ecosystem service value of riparian zone using land use data from 1986 to 2012. (October 2016) - Fu, Bolin; Li, Ying; Wang, Yeqiao; Zhang, Bai; Yin, Shubai; Zhu, Honglei; Xing, Zefeng
Highlights: Quantification of ecosystem service value (ESV) of riparian zone used land use data. NDVI and pearl growth curve (PGC) model allow the modification of value coefficients. The total ESV increased by 76.9 million (USD) from 1986 to 2012. The contribution to ESV from wetland decreased 19.8% during the study period. Willingness to pay for ecosystem services increased at a slower rate than economic development. Abstract: Riparian zones play a significant role in ecological and biological sciences, as well as in environmental management and engineering perspectives because of their multiple functions in coupled natural and human systems. Quantitative evaluation of ecosystem service value (ESV) is essential to maintain the ecological functions that riparian areas provide. This manuscript addressed the overlap and connections among anthropogenic impacts (land use) with evaluations of societal benefits through ESV to an environmentally sensitive riparian zone in Northeast China using remote sensing observations and socio-economic data. The reported study evaluated the trend of ESV change in the riparian zone from 1986 to 2012. The procedures included (1) assignment of equivalent weight factors per unit hectare of terrestrial ecosystem services in the riparian zone; (2) calculation of ESV coefficients per unit area; (3) estimation of the total ESV in the riparian zone and exploration of the trend of the riparian ESVs from 1986 to 2012. The results were that the total ESV in the study area increased from $42.30 million (USD) in 1986 to $119.17 million (USD) in 2012. An average ESV of individual basic evaluation units increased from $0.08 million (USD) in 1986 to $0.3 million (USD) in 2012.